Cuddle Weather: Mga Tula - Aguinaldo, Dennis Andrew S. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
Taken together, the three poems collect resolve as the government fails its people, the medical system buckles, lockdowns isolate, and condolences proceed without letup. This, in the fashion of a child pooling courage before a syringe.